The Latent Organizational Functions of the Academic Senate Why Senates Don't Work but Won't Go Away. ASHE 1987 Annual Meeting Paper - Birnbaum, Robert ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1987)
The roles of academic senates in university organization are discussed. Three symbolic purposes that academic senates may fill are considered first: they may symbolize institutional membership in the higher education system, collective and individual faculty commitment to professional values, and joint faculty-administration acceptance of existing authority relationships. Serving on the academic senate can confer status that protects the institution from two disruptive elements, informal leaders and organizational deviants. Since academic senates typically take a long time to make decisions, complicated problems that administrators prefer not to tackle can be directed to the senate, where the problem goes into an organizational "deep freeze." Since most items that someone wants discussed by the senate are never acted upon, the use of the senate as an attention cue is a good way to allocate attention. The senate, by inhibiting the propensity to change that increasingly characterizes the administration, serves as a major element in the homeostatic process of organizational conservation. Other roles of the senate include: a personnel screening device, a ritual and pastime, and scapegoat. These functions of the senate are considered in the context of the model of organized anarchy. (SW)
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
ERIC Note: Paper presented at the Annual Meeting of the Association for the Study of Higher Education (San Diego, CA, February 14-17, 1987).
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Governing Councils; Faculty College Relationship; Governance; Higher Education; Models; Organizational Effectiveness; Organizational Theories; Political Influences; Teacher Administrator Relationship; ASHE Annual Meeting; Opinion Papers; Speeches/Meeting Papers